2017
DOI: 10.1002/cplu.201700251
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Polyoxometalate Ionic Liquids against Clinically Relevant Pathogens

Abstract: The activity of a new class of antimicrobials—polyoxometalate ionic liquids (POM‐ILs)—is systematically investigated. The prototype POM‐ILs feature Keggin‐type anions (α‐SiW11O398−) and tetraalkylammonium ions as active cationic species. Antimicrobial tests of the POM‐ILs against important human pathogens show that variation of the alkyl chain length of the cation leads to significant changes in antimicrobial activity against the medically relevant Gram‐negative bacteria Escherichia coli and Pseudomonas aerugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 49 publications
1
30
0
8
Order By: Relevance
“…In sum, PS microplastics removal by magnetic particle attachment could provide ameans of treating larger volumes of water which are not amenable to classical filtration. [21] Some of our previous research has confirmed the bactericidal properties of POM-ILs, [10,12,25] therefore we hypothesized that magPOM-SILP 2 would be able to purify water heavily contaminated with bacteria. Thea ntibacterial water purification properties of the magPOM-SILPs were tested against gram-negative E. coli and gram-positive B. subtilis.…”
Section: Angewandte Chemiementioning
confidence: 93%
See 2 more Smart Citations
“…In sum, PS microplastics removal by magnetic particle attachment could provide ameans of treating larger volumes of water which are not amenable to classical filtration. [21] Some of our previous research has confirmed the bactericidal properties of POM-ILs, [10,12,25] therefore we hypothesized that magPOM-SILP 2 would be able to purify water heavily contaminated with bacteria. Thea ntibacterial water purification properties of the magPOM-SILPs were tested against gram-negative E. coli and gram-positive B. subtilis.…”
Section: Angewandte Chemiementioning
confidence: 93%
“…Thea ntibacterial water purification properties of the magPOM-SILPs were tested against gram-negative E. coli and gram-positive B. subtilis. [12] Briefly,aqueous solutions of the microporous magPOM-SILP 2 were inoculated with 10 6 CFU mL À1 of E. coli or B. subtilis and incubated at 37 8 8Cf or 1hbefore removing the particles with am agnet and quantifying the bacteria present in the supernatant solutions.AtamagPOM-SILP 2 concentration of 1mgmL À1 ,t he bacterial removal was 58 %f or E. coli and 100 %f or B. subtilis,w hile at ac oncentration of 10 mg mL À1 the bacterial removal efficiency was 100 %for both bacterial strains.T he antibacterial effect was confirmed and characterized using electron microscopies (SEM and TEM). Ther eusability of the magPOM-SLIP nanoparticles was tested over three cycles of inoculation with E. coli or B. subtilis,p article separation, and particle washing with water and subsequent reuse with af resh inoculum of the bacteria.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Sein Forschungsinteresse gilt der Chemie der Polyoxometallate und ihrem Einbau in funktionelle Komposite für Katalysezwecke, der Sonnenenergiekonversion, der elektrochemischen Energiespeicherung und fortschrittlichen multifunktionellen Materialien. In der Angewandten Chemie hat er Polyoxometallat‐Nickelschaum‐Elektroden beschrieben und in ChemPlusChem die antimikrobielle Aktivität von organischen Flüssigkeiten auf Polyoxometallatbasis …”
Section: Ausgezeichnet …unclassified
“…Over the last decades, POMs were proposed as promising candidates for new antidiabetic, anti‐Alzheimer, anticancer and antiviral drugs. They were identified as antibacterial agents, either in pure form, as ionic liquid or in association with commercial antibiotics …”
Section: Introductionmentioning
confidence: 99%